When dysphoria is not a primary mental state: A case report of the role of the aromatic L-aminoacid decarboxylase. Issue 22 (June 2018) - Portaro, Simona; Gugliandolo, Agnese; Scionti, Domenico; Cammaroto, Simona; Morabito, Rosa; Leonardi, Salvatore; Fraggetta, Filippo; Bramanti, Placido; Mazzon, Emanuela
Abstract: Rationale: The aromatic L-amino acid decarboxylase (AADC) deficiency (AADCD) is a rare, autosomal recessive neurometabolic disorder caused by a deficit of the AADC that is involved in serotonin and dopamine biosynthesis, causing as a consequence, their deficits, but also a lack of norepinephrine and epinephrine, given that dopamine is their precursor. Patient concerns: We report the case of a Caucasian 43-year-old woman heterozygous for p.Ser250Phe in DDC, encoding for AADC with a positive family history for behavioral problems. Diagnoses: Since adolescence, she manifested behavioral abnormalities. Three months before the admission to our hospital, she presented with a permanent dystonic posture at the 4 limbs with numbness and tingling, diplopia, and low potassium levels. She was treated with muscle relaxants and potassium, but with no results. Olanzapine was administrated, worsening mood problems. Later, after fever, low potassium levels, and increased difficulty to move, she was admitted to the neurology unit where, after bradycardia alternating with atrial and ventricular fibrillation, she had loss of consciousness. She started to complain involuntary parossistic eye and head movements, bilateral ptosis, oculogyric crises with dystonia of the head, muscle hypotrophy, and absent deep tendon reflexes. During the hospital stay, she continued having episodes of untreatable bradycardia and fever. Interventions: Hemocultures were performed, resulting positive for Enterococcus faecalis and Acinetobacter baumanii . Whole exome sequencing was performed evidencing that the patient harbored the heterozygous p.Ser250Phe variant in the gene DDC. Outcomes: A treatment with Pyridoxine and Pramipexole was prescribed, but never started because she died. Lessons: The heterozygosity for p.Ser250Phe may have influenced the clinical manifestations, given that the patient presented some overlapping symptoms with those in AADCD, but while AADCD normally is diagnosed during childhood, the fact that the patient carried the mutation in heterozygosity may have alleviated and delayed the clinical manifestations.